New hybrid cycloconverters: an evaluation of their performance - Xu, Tianning (2009)
Nowadays, power electronic converters based exclusively on IGBTs seem to have achieved excellent load side performance up to megawatt powers range in the low voltage range (200-690Vrms) and are steadily gaining good performance in the medium voltage range as well. However, the medium and high voltage/high power range remains dominated by converters using naturally commutated thyristors, such as line-commutated cycloconverters, line-commutated current source inverters, which provide comparatively poorer output side performance. The purpose of this thesis is to investigate both the conventional cycloconverter, which will be referred as standard cycloconverter in the thesis, and the new hybrid cycloconverter topologies, which are capable of improving the performance of the standard cycloconverter by adding an auxiliary forced commutated inverter with reduced installed power. It will be shown that the new topology is not only able to improve the quality of the output voltage, but also to enhance the control over the circulating current and therefore, for some of the standard cycloconverter arrangements, to improve the input power quality.